A highly selective and sensitive turn-on fluorescent probe for the detection of holmium ion and its bioimaging1. Issue 14 (19th February 2015) - Guo, Yanqing; Huo, Fangjun; Yin, Caixia; Kang, Jin; Li, JianFang
<x xml:space="preserve">Abstract</x> The phenolphthalein aldehyde was synthesized and used to a turn-on fluorescent probe for the detection of holmium ion (Ho3+) in HEPES : DMF = 1 : 1 (v/v pH = 7.4) solution with an excellent selectivity and sensitivity for Ho3+ over other metal ions.